A Case Series on Pilon Fractures Treated Using the Limb Reconstruction System - Vasanthkumar Chandrakumar; Suriya Kulothungan Karikalan; Sasikumar Kumar; Venkata Kiran Pillella (Journal of Orthopedics and Joint Surgery)
Introduction: Amid the most challenging fractures to properly treat are tibia fractures. The degree of comminution, soft tissue status, and contamination level suffered during the injury influence the functional outcome. Surgical intervention aims to achieve a proper reduction of the tibia while maintaining sufficient stability to permit ankle movements. To reduce treatment problems, this should be done with methods that limit the devascularization of the soft and osseous tissues. Methods and results: A prospective study was conducted on 14 patients hospitalized with closed tibial pilon fractures managed using the limb reconstruction system (LRS) at Sree Balaji Medical College and Hospital. The range of ankle motion on average is dorsiflexion ranges 5–14° and plantarflexion ranges 5–20°. Clinical outcomes were graded as excellent (90–100), good (80–89), satisfactory (70–79), sufficient (60–69), or low (<60) according to the Mazur ankle score. The average score was 88.8 (good). Type 3 fractures were found to have poor clinical outcomes when compared to type 1 and type 2 fractures. Conclusion: Due to LRS’s cost-effectiveness, patient-friendliness, versatility, and safety, it is considered an excellent method for managing closed tibial pilon fractures as the primary and definitive mode.